The effects of disturbance on the external mycelium of arbuscular mycorrhizal fungi on plant growth - Martins, Marco Antonio; Read, David John (Pesquisa Agropecuaria Brasileira, 1997)
An experiment with different levels of disturbance on the external mycelium of arbuscular mycorrhizal (AM) fungi was carried out in order to test the hypothesis that AM root colonization can be initiated through the external mycelium which provides the plants with access to P and stimulate its growth. The results revealed that the intact external mycelium of AM fungi represents a vigorous source of inoculum, the disruption or detachment of which reduces its inoculum potential, without eliminating its infectivity. The intact external mycelium enhances the absorption of phosphate ions from soil, a process which can be temporarily inhibited, with adverse consequences for plant growth, if the mycelium is disrupted.